Production of 68Ga-citrate Based on a SnO2 Generator for Short-Term Turpentine Oil-Induced Inflammation Imaging in Rats - Mirzaei, Alireza; R. Jalilian, Amir; Akhlaghi, Mehdi; Beiki, Davood (Current Radiopharmaceuticals, 2016)
Introduction: Gallium-68 citrate has been successfully applied in the PET imaging of infections and inflammation in some centers; however further evaluation of the tracer in inflammation models is of great importance. Methods: 68Ga-citrate prepared from [68Ga]GaCl3 (eluted form an SnO2 based 68Ge/68Ga generator) and sodium citrate at optimized conditions followed by quality control tests was injected to normal and turpentine-oil induced rats PET/CT imaging studies up to 290 min. Results: 68Ga-citrate was prepared with acceptable radiochemical purity (>99 ITLC, >99% HPLC), specific activity (28-30 GBq/mM), chemical purity (Sn, Fe <0.3 ppm; Zn<0.2 ppm) in 15 min at 50°C. PET/CT imaging of the tracer demonstrated early detection of inflamed site in animal models in 60-80 min. Conclusion: This study demonstrated possible early detection of inflammation foci in vivo using 68Ga-citrate prepared using commercially available 68Ge/68Ga generators for PET imaging.
Keywords: 68Ga-citrate